2005
DOI: 10.1097/01.brs.0000174275.95104.12
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro, Biomechanical Comparison of an Anterior Lumbar Interbody Fusion with an Anteriorly Placed, Low-Profile Lumbar Plate and Posteriorly Placed Pedicle Screws or Translaminar Screws

Abstract: Although not as rigid as pedicle or translaminar screws, anterior lumbar plating does add significant stability to an ALIF and may provide a valuable, single-approach alternative to supplemental posterior fixation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
45
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(49 citation statements)
references
References 31 publications
2
45
0
Order By: Relevance
“…Interbody fusion can be carried out through the anterior or posterior approach. Though high fusion rates have been reported with the anterior approach, the possibility of iliac vessel injury and retrograde ejaculation cannot be overlooked [3,16,17]. Further, studies have recommended that anterior lumbar interbody fusion (ALIF) be supplemented with posterior instrumentation for higher fusion rates [21].…”
Section: Discussionmentioning
confidence: 99%
“…Interbody fusion can be carried out through the anterior or posterior approach. Though high fusion rates have been reported with the anterior approach, the possibility of iliac vessel injury and retrograde ejaculation cannot be overlooked [3,16,17]. Further, studies have recommended that anterior lumbar interbody fusion (ALIF) be supplemented with posterior instrumentation for higher fusion rates [21].…”
Section: Discussionmentioning
confidence: 99%
“…1,44 Moreover, a transsacral rod enhanced with pedicle screws has been shown to reduce the range of motion to levels comparable to anterior interbody fusion cages augmented with a similar posterior construct in biomechanical testing. 2,6 However, although the short-term biomechanical stability of the AxiaLIF device combined with posterior instrumentation appears to be solid, the threads of the axial rod may be inadequate to provide long-term structural support. This would be consistent with the findings in the current study; we noticed a transient increase in height of the L5/S1 intervertebral space following implantation of the AxiaLIF device.…”
Section: Discussionmentioning
confidence: 99%
“…1,44 Concurrently, cadaver studies have demonstrated that circumferential instrumentation performed using the AxiaLIF device in combination with posterior fixation provides biomechanical stability similar to anterior interbody fusion cages augmented with a posterior construct. 2,6 Although the paracoccygeal transsacral approach is not without risks and there is a potential for visceral and vascular injuries, 12,39,55 the reported rates of perioperative morbidity are low. 3,5,27,58,59 However, a recent report raised serious concerns regarding the long-term durability of 2-level AxiaLIF constructs.…”
mentioning
confidence: 99%
“…The advantages to pure moment testing lie in its consistency as an accepted standard protocol across previous literature (Wilke et al, 1998(Wilke et al, , 2001 and its ability to ensure uniform loading across all levels of the spinal column. Among the set-ups currently used to apply pure bending moments (Beaubien et al, 2005;Crawford et al, 1995;DiAngelo et al, 2004;Goel et al, 1988;Kotani et al, 2006;Melcher et al, 2002;Panjabi et al, 2007;Puttlitz et al, 2004;Schwab et al, 2006;Stanley et al, 2004;Wilke et al, 1994), the cable-driven (Acosta et al, 2008;Barnes et al, 2009;Panjabi, 2007) is relatively common due to its minimal requirements and ease of use. This system involves a loading ring attached to one end of the spinal segment and connected to the test frame's actuator head via a cable.…”
Section: Introductionmentioning
confidence: 99%